Optical Transport Network to support Digital Communications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this work is to propose a solution to the problem of the lack of telecommunication services, with adequate quality of service and coverage, in the town of Choclococha, Huancavelica-Peru. For this purpose, the design and evaluation of an optical link as a backbone network and a wireless access network is presented. It is an applied and experimental research in which performance parameters were evaluated. The independent variable is the optical transport network and the dependent variable is data communication. The latter is defined by two indicators: throughput and signal reception power at the users. Both indicators were measured in a sample of the population, obtaining results that were validated with respect to the expected values according to specifications and regulations. Thus, the measured throughput exceeds the 40% data rate guaranteed by the telecommunications operator. As for the reception power, it exceeds the sensitivity level of the receiving equipment. Therefore, it is concluded that the proposed solution supports communications with optimum speed and coverage.